EULAR/PRES recommendations for vaccination of paediatric patients with autoimmune inflammatory rheumatic diseases: update 2021. Issue 1 (20th June 2022) - Jansen, Marc H A; Rondaan, Christien; Legger, Geertje E; Minden, Kirsten; Uziel, Yosef; Toplak, Natasa; Maritsi, Despoina; van den Berg, Lotte; Berbers, Guy A M; Bruijning, Patricia; Egert, Yona; Normand, Christophe; et al.
Abstract : Objectives: Recent insights supporting the safety of live-attenuated vaccines and novel studies on the immunogenicity of vaccinations in the era of biological disease-modifying antirheumatic drugs in paediatric patients with autoimmune/inflammatory rheumatic diseases (pedAIIRD) necessitated updating the EULAR recommendations. Methods: Recommendations were developed using the EULAR standard operating procedures. Two international expert committees were formed to update the vaccination recommendations for both paediatric and adult patients with AIIRD. After a systematic literature review, separate recommendations were formulated for paediatric and adult patients. For pedAIIRD, six overarching principles and seven recommendations were formulated and provided with the level of evidence, strength of recommendation and Task Force level of agreement. Results: In general, the National Immunisation Programmes (NIP) should be followed and assessed yearly by the treating specialist. If possible, vaccinations should be administered prior to immunosuppressive drugs, but necessary treatment should never be postponed. Non-live vaccines can be safely given to immunosuppressed pedAIIRD patients. Mainly, seroprotection is preserved in patients receiving vaccinations on immunosuppression, except for high-dose glucocorticoids and B-cell depleting therapies. Live-attenuated vaccines should be avoided in immunosuppressed patients. However, it is safe to administer the measles–mumps–rubella booster and varicella zoster virus vaccine to immunosuppressed patients under specific conditions. In addition to the NIP, the non-live seasonal influenza vaccination should be strongly considered for immunosuppressed pedAIIRD patients. Conclusions: These recommendations are intended for paediatricians, paediatric rheumatologists, national immunisation agencies, general practitioners, patients and national rheumatology societies to attain safe and effective vaccination and optimal infection prevention in immunocompromised pedAIIRD patients.